Telemedicine and Telementoring in Rhinology, Otology, and Laryngology: A Scoping Review. Issue 1 (March 2022) - Yang, Angela; Kim, Dayoung; Hwang, Peter H.; Lechner, Matt
Objective: Telemedicine and telementoring have had a significant boost across all medical and surgical specialties over the last decade and especially during the COVID-19 pandemic. The aim of this scoping review is to synthesize the current use of telemedicine and telementoring in otorhinolaryngology and head and neck surgery. Data Sources: PubMed and Cochrane Library. Review Methods: A scoping review search was conducted, which identified 469 articles. Following full-text screening by 2 researchers, 173 articles were eligible for inclusion and further categorized via relevant subdomains. Conclusions: Virtual encounters and telementoring are the 2 main applications of telemedicine in otolaryngology. These applications can be classified into 7 subdomains. Different ear, nose, and throat subspecialties utilized certain telemedicine applications more than others; for example, almost all articles on patient engagement tools are rhinology based. Overall, telemedicine is feasible, showing similar concordance when compared with traditional methods; it is also cost-effective, with high patient and provider satisfaction. Implications for Practice: Telemedicine in otorhinolaryngology has been widely employed during the COVID-19 pandemic and has a huge potential, especially with regard to its distributing quality care to rural areas. However, it is important to note that with current exponential use, it is equally crucial to ensure security and privacy and integrate HIPAA-compliant systems (Health Insurance Portability and Accountability Act) in the big data era. It is expected that many more applications developed during the pandemic are here to stay and will be refined in years to come.